D.07 Clinical electromyography training in Canada: The experience of neurology and physiatry residents. (17th June 2016) - Berger, MJ; Florendo-Cumbermack, AG; Gray, DA; Côté-Mantha, É; Chapman, K; Winston, P; Venance, S
Abstract : Background: There are currently no national standards for clinical electromyography (EMG) training for residents in neurology and physiatry in Canada. The purpose of this study was to obtain demographic and qualitative data pertaining to EMG residency training in Canada, with the goal of facilitating discourse that could lead to national standards for EMG training.Methods: An online survey was distributed to senior neurology and physiatry residents (post-graduate years 3-5), at seven tertiary Canadian centres. The study authors, who are trainees and consultants with a broad range of EMG expertise (junior and senior resident, clinical neuromuscular fellows, senior physiatrist and neuromuscular neurologists), developed pertinent demographic and qualitative questions.Results: Thirty-eight residents completed the survey (23 neurology, 15 physiatry). There was inter-program variation in quantity of the training experience, content of the curriculum, access to expertise (including technologists) and goals for future training and practice. Similarly, differences were identified between the training experiences of neurology and physiatry residents.Conclusions: Inter-program variability in EMG training was identified. Additionally, differences were identified between neurology and physiatry resident training. This data provides evidence of training discrepancies across the country and can be used to establish national training standards for EMG in Canada.